Influences of a high excitation frequency (70 MHz) in the glow discharge technique on the process plasma and the properties of hydrogenated amorphous silicon - Finger, F.; Kroll, U.; Viret, V.; Shah, Arvind; Beyer, W.; Tang, X.-M.; Weber, J.; Howling, A. A.; Hollenstein, C. (My University, 1992)
Hydrogenated amorphous silicon has been prepared at a plasma excitation frequency in the very-high-frequency band at 70 MHz with the glow discharge technique at substrate temperatures between 280 and 50 °C. The structural properties have been studied using hydrogen evolution, elastic recoil detection analysis, and infrared spectroscopy. The films were further characterized by dark and photoconductivity and by photothermal deflection spectroscopy. With respect to films prepared at the conventional frequency of 13.56 MHz considerable differences concerning the electronic and structural properties are observed as the substrate temperature is decreased from 280 to 50 °C. Down to a substrate temperature of 150 °C the electronic film properties change only a little and the total hydrogen content cH and the degree of microstructure that can be directly correlated to cH increase only moderately. Below 150 °C the electronic properties deteriorate in the usual manner but still the total hydrogen content does not exceed 21 at. % even at a substrate temperature of 50 °C. It is argued that the influence of the higher excitation frequency on the plasma and on the growth kinetics plays a key role in this context by allowing a highly effective dissociation of the process gas with the maximum ion energies remaining at low levels. It is concluded that deposition processes at higher excitation frequencies can have important technological implications by allowing a decrease of the deposition temperature without losses in the material quality.